A little bit of charm [large type] - Ellis, Mary, 1951- (The New Beginnings Series, 2013)
Rachel King leaves Lancaster County to join her cousin in Kentucky, where she works at a stable and meets the English Jake, whom she is attracted to despite fearing that he is responsibile for the accidents that plague her Amish suitors.